2017
DOI: 10.1016/j.appet.2016.08.114
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the attention control training program on reducing attentional bias in obese and overweight dieters

Abstract: Evidence indicates that attentional bias and dieter's eating styles (i.e., external, emotional, restraint) play important roles in the success or failure of dieters. First, we studied food-related attentional bias (FAB; based on interference scores on a modified Stroop test), eating styles (Dutch Eating Behavior Questionnaire), and increases in body mass index (BMI) in overweight or obese dieters (n = 34) and nondieters (n = 35). Compared with nondieters, dieters showed higher FAB, which was positively associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 59 publications
0
46
0
Order By: Relevance
“…Interestingly, they found a paradoxical effecttraining bias towards unhealthy food induced higher proportion of low fat options, probably due to demand characteristics. Two other studies examined the effectiveness of a single session of active AtBM training compared to Standard Control conditions for reducing unhealthy eating behaviors, BMI and diet failure rate in university students with excess weight (Bazzaz et al, 2017;Hardman et al, 2013). Specifically, Hardman and colleagues found modest effects of active AtBM training on attentional bias to food images, and no effects on subjective levels of hunger and food intake, as measured by an analogue scale and a food preference test, respectively (Hardman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, they found a paradoxical effecttraining bias towards unhealthy food induced higher proportion of low fat options, probably due to demand characteristics. Two other studies examined the effectiveness of a single session of active AtBM training compared to Standard Control conditions for reducing unhealthy eating behaviors, BMI and diet failure rate in university students with excess weight (Bazzaz et al, 2017;Hardman et al, 2013). Specifically, Hardman and colleagues found modest effects of active AtBM training on attentional bias to food images, and no effects on subjective levels of hunger and food intake, as measured by an analogue scale and a food preference test, respectively (Hardman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Hardman and colleagues found modest effects of active AtBM training on attentional bias to food images, and no effects on subjective levels of hunger and food intake, as measured by an analogue scale and a food preference test, respectively (Hardman et al, 2013). Bazzaz and colleagues (2017) found that the Active Training reduced BMI and diet failure rate, i.e., number of participants who quitted their diet from pretest to posttest and to the follow-up test (Bazzaz et al, 2017). Moderation analyses showed that high levels of restraint moderated the positive effect of the Active Training on BMI loss, particularly in those dieters with high levels of restraint.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater attention to food also occurs in overweight and obese individuals that are dieting vs. not dieting (Bazzaz, Fadardi, & Parkinson, 2017). This may explain why tDCS was not as effective at reducing food consumption in those with higher intent to restrict as measured by the DEBQ-R, but significantly reduced eating in those with lower intent to restrict scores.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that people with obesity and/or with BED tend to have AB towards food cues together with a difficulty in disengaging from these cues (as measured with eye tracking techniques) (11). Importantly, gaze maintenance on food cues has been shown to contribute to food cravings and to subsequent food consumption (10,16) and AB has been positively associated with body mass index (BMI) (17). Due to the potential role of AB in eating behaviour, treatment approaches aimed at modifying these biases, have been developed (18,19).…”
Section: Introductionmentioning
confidence: 99%